2023
DOI: 10.1002/vetr.2995
|View full text |Cite
|
Sign up to set email alerts
|

Determining a cut‐off point for intervention analgesia in rabbits using the Bristol Rabbit Pain Scale

Abstract: BackgroundThe objective of this study was to determine the threshold of the Bristol Rabbit Pain Scale (BRPS) indicating the need for intervention analgesia.MethodsFourteen members of veterinary staff were recruited to rate rabbits (n = 71) in acute pain. Observers in group A (n = 7) were asked to score each rabbit using the BRPS, while observers in group B (n = 7) independently answered the question ‘In your clinical capacity, do you think this animal requires analgesia?’ with either 'Yes' or 'No'. The answers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Benato et al 7,9 Previously demonstrated that BRPS is a clinically valid and reliable tool for quantifying pain in rabbits. Rabbits with pain scores of ≥ 5 points on the BRPS were recommended for analgesic intervention.…”
Section: Ablation Proceduresmentioning
confidence: 99%
“…Benato et al 7,9 Previously demonstrated that BRPS is a clinically valid and reliable tool for quantifying pain in rabbits. Rabbits with pain scores of ≥ 5 points on the BRPS were recommended for analgesic intervention.…”
Section: Ablation Proceduresmentioning
confidence: 99%